USTADZ: GENRE BARU DALAM STRUKTUR BUDAYA MASYARAKAT MADURA - Edi Susanto Edi Susanto (Institut Agama Islam Negeri Madura)
Abstrac This article tries to describe the dynamics of socio-religion of contemporary Madurese society that experience social-cultural diversification and differentiation. Ustadz (muslim teacher) appears the outstanding issue in it. The term of ustadz broadens and develops in meaning. Previously, the terminology of ustadz identified dependent and un-autonomous position. However, this term become more independent and more autonomous in its position currently. This also turns out to be a